Design of electron gun with a current of 50 mA for use in a dynamitron accelerator - M Gholami Akbarabad; M.R Ghasemi; A.A Shokri; A Grayli (مجله علوم و فنون هسته‌ای, 2019)
This paper presents the design of a thermionic electron gun with two different geometries, flat cathode and spherical cathode.The purpose of this research is to answer the question of which type of electron gun is suitable for industrial electrostatic accelerators. CST Studio software was used to design the guns. The desired specification in the design of a suitable thermionic gun, the maximum current  of  50 milliamper and the voltage 5 to 10 kilovolt, is selected for use in the dynamitron accelerator. The beam current, the waist beam radius, the waist beam position and the perveance of a flat cathode gun and spherical cathode gun were 49 and 49.8 mA, 3.2 and 0.45 mm, 36 and 24.3mm, 0.138 and 0.0498 μperv, respectively. Since the electron guns used in the industry have a perveance between 0.1 to 1 μperv therefore, an electron gun with a flat cathode with 0.138 μperv is more suitable.  On the other hand, it is easier and less costly to make it. That is why the gun with a flat cathode was chosen and its final dimensions are presented.